MANAJEMEN PENGEMBANGAN INDUSTRI BATIK GROBOGAN SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT - Maimunah, Elistriany Intar; Hidayat, Zainal; Priyadi, Budi Puspo (Journal of Public Policy and Management Review, 2021)
Abstract The development of batik is currently a serious problem in Grobogan Regency due to the lack of competitiveness of grobogan batik quality. The lack of attractiveness of the public to buy batik products led to a decrease in the amount of production. This research aims to analyze management in the development of Grobogan batik industry as an effort to empower the community and the factors that are the obstacles. This research uses qualitative descriptive method with data collection techniques using interview, observation and documentation techniques. The research looked at the management component in the development of Grobogan batik industry as a community empowerment effort that includes planning, organizing, actuating, controlling owned by George R. Terry, and wilson's theory of empowerment process. The results showed that the management of the development of the Grobogan batik industry as an effort to empower the community in Grobogan Regency is good enough although still not maximal because of activities that only focus on monotonous coaching and lack of innovations that can attract more people to participate. The factors that influence are: weak public awareness, lack of community participation rate, lack of ability to use technology, traditional mindset of society, people still market batik products with conventional, and lack of public attraction so that there needs to be more opportunities for the community to increase participation, there is still a feeling of excessive sungkan and innovation and expansion of cooperation with the marketplace. The suggestions provided are: provide space and opportunities for the community in conveying aspirations, developing innovations by bringing professional speakers in sustainable seminars, providing market place training, conducting open surveillance reporting uploaded through the Disperindag web, as well as marketing Grobogan batik products, in tourist attractions. Keywords: